2004
DOI: 10.1542/peds.2004-0092
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Benefits of Continuous Subcutaneous Insulin Infusion in Very Young Children With Type 1 Diabetes: A Follow-up Report

Abstract: CSII is a durable and effective means of optimizing glycemic control in very young patients with type 1 diabetes and may be superior to multiple daily injections in minimizing the risk of severe hypoglycemia in this age group. Employment of paid caregivers does not preclude safe and effective use of CSII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(136 citation statements)
references
References 26 publications
10
119
1
6
Order By: Relevance
“…Doyle et al (2004) 110 reported an insignificant difference -0.6 units/kg per day on CSII and 0.7 units/kg per day on MDI. Thomas et al (2007) 111 reported the daily insulin dose at zero and 24 weeks.…”
Section: Quality Of Lifementioning
confidence: 97%
See 4 more Smart Citations
“…Doyle et al (2004) 110 reported an insignificant difference -0.6 units/kg per day on CSII and 0.7 units/kg per day on MDI. Thomas et al (2007) 111 reported the daily insulin dose at zero and 24 weeks.…”
Section: Quality Of Lifementioning
confidence: 97%
“…Doyle et al (2004) 110 recruited children and adolescents with T1DM, age range 8-21 years. None had been on glargine or CSII before, and most were on conventional twice-daily insulins.…”
Section: Csii Versus Analogue Mdiquantity Of Research Availablementioning
confidence: 99%
See 3 more Smart Citations